2021
DOI: 10.1186/s13099-021-00448-y
|View full text |Cite
|
Sign up to set email alerts
|

The use of biomarkers associated with leaky gut as a diagnostic tool for early intervention in autism spectrum disorder: a systematic review

Abstract: Background Innovative research highlighted the probable connection between autism spectrum disorder (ASD) and gut microbiota as many autistic individuals have gastrointestinal problems as co-morbidities. This review emphasizes the role of altered gut microbiota observed frequently in autistic patients, and the mechanisms through which such alterations may trigger leaky gut. Main body Different bacterial metabolite levels in the blood and urine of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
1
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 129 publications
0
42
1
4
Order By: Relevance
“…When the ASD mice were treated with candidate microbial metabolites, their abnormal behaviour improved significantly, and the excitability of brain neurons were regulated [ 100 ]. A Systematic review found that altered gut microbiota in autistic children may trigger intestinal leakage, of which short-chain fatty acids, lipopolysaccharide, calprotectin, lysozyme and lysozyme can be used as biomarkers for early detection of intestinal leakage [ 101 ]. This indicates that gut microbiota could be a target for ASD treatment.…”
Section: Discussionmentioning
confidence: 99%
“…When the ASD mice were treated with candidate microbial metabolites, their abnormal behaviour improved significantly, and the excitability of brain neurons were regulated [ 100 ]. A Systematic review found that altered gut microbiota in autistic children may trigger intestinal leakage, of which short-chain fatty acids, lipopolysaccharide, calprotectin, lysozyme and lysozyme can be used as biomarkers for early detection of intestinal leakage [ 101 ]. This indicates that gut microbiota could be a target for ASD treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Various pathologies involving neuroinflammation can result in BBB failure [ 26 , 44 , 45 , 49 , 50 , 51 , 52 , 53 , 54 ]. BBB integrity may also be affected by alterations of gut microbiota and increased gut permeability, as reported in ASD patients [ 27 , 55 ]. This dysfunction allows inflammatory mediators, bacteria, and xenobiotics to pass into the blood stream, contributing to neuroinflammation in ASD patients [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…BBB integrity may also be affected by alterations of gut microbiota and increased gut permeability, as reported in ASD patients [ 27 , 55 ]. This dysfunction allows inflammatory mediators, bacteria, and xenobiotics to pass into the blood stream, contributing to neuroinflammation in ASD patients [ 27 ]. Microbiome alterations may also be associated with gastrointestinal disturbances, frequently reported in ASD [ 28 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Also, increased intestinal permeability (“leaky gut”) in patients with ASD, potentially related to abnormal microbiome, were observed in a study showing that 43% of children with ASD compared to 0% of the controls presented an abnormal mannitol:lactulose test ( D'Eufemia et al, 19921996 ). Disrupted gut–blood–brain barriers may allow bacteria metabolites and other substances to get into the bloodstream and, subsequently, alter the brain ( Al-Ayadhi et al, 2021 ).…”
Section: Main Textmentioning
confidence: 99%